Monitoring thrombin generation: Is addition of corn trypsin inhibitor needed? - Spronk, Henri M. H.; Dielis, Arne W. J. H.; Panova-Noeva, Marina; Oerle, René van; Govers-Riemslag, José W. P.; Hamulyák, Karly; Falanga, Anna; Cate, Hugo Ten (Thrombosis and Haemostasis, 2009)
Thrombin generation monitoring has the potential to be used as a clinical diagnostic tool in the near future. However, robust pre-analytical conditions may be required, and one factor that has been reported is in-vitro contact activation that might influence in-vitro measurements of thrombin generation and thereby act as an unpredictable pre-analytical variable. The aim of the current study was to investigate the influence of contact activation and the necessity of corn trypsin inhibitor (CTI) to abolish contact activation in thrombin generation measurements at low tissue factor (TF) concentrations. Thrombin generation was performed using the calibrated automated thrombinoscopy (CAT), thereby determining the endogenous thrombin potential (ETP), peak height, and the lag time, in plasma obtained from healthy volunteers. Addition of CTI after plasma preparation had no significant influence on thrombin generation triggered with 0.5 pM TF or higher, as demonstrated by unaltered ETP and lag time values between analyses with and without CTI. Addition of CTI before blood collection reduced thrombin generation triggered with 0.5 pM TF: both the ETP and peak height were significantly reduced compared to no CTI addition. In contrast, thrombin generation remained unaltered at a 1 pM TF trigger or above. This study demonstrates that addition of CTI after plasma separation is not necessary when triggering with TF concentrations of 0.5 pM and higher. Furthermore, it was demonstrated that it is not needed to pre-fill blood collecting tubes with CTI when measuring thrombin generation at TF concentrations of ≥1 pM.
Keywords: Thrombin generation; calibrated automated thromborgam; corn trypsin inhibitor